The hanged man = [El ahorcado] - Caffey, Michael; Trevey, Ken; Forrest, Steve, 1925-2013; Jagger, Dean, 1903-1991; Bing Crosby Productions; Cinetel Films ([Los Angeles, CA] : Bing Crosby Productions, Inc., 1974)
A gunfighter survives his own hanging and discovers that he has the power to read people's minds. He decides to use his powers to help people, and comes across a young widow who is trying to keep a ruthless land baron from taking her ranch.
Originally broacast on ABC as a television movie in 1974.
"A Fenday Associates production in association with Bing Crosby Productions."
Steve Forrest, Dean Jagger, Will Geer, Sharon Acker, Brendon Boone, Rafael Campos, Barbara Luna, Cameron Mitchell.
Cinematographer, Keith C. Smith; editor, Nick Archer; music, Richard Markowitz.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Hanging -- Drama; Telepathy -- Drama; Silver mines and mining -- Drama; Shooters of firearms -- Drama; Widows -- Drama; West (U.S.) -- Drama; Made-for-TV movies; Western films; Feature films; Fiction films; Internet videos; Streaming video